Antibacterial Activity of Endophytic Fungi Isolated from Mangrove Plant Sonneratia griffithii Kurz - Dian Handayani, Harrizul Rivai, Monica Hutabarat, Roslaili Rasyid (Journal of Applied Pharmaceutical Science, 2017)
The aim of this study was focused on the antibacterial activity of endophytic fungi from leaf, bark and root of mangrove Sonneratia grifithii Kurz, collected from Bungus, West Sumatra. Isolation of endophytic fungi was based on direct planting method with sabouraud dextrose agar (SDA) as growth medium. Twelve isolates fungi strains were obtained from this mangrove. They were cultivated on sabouraud dextrose broth (SDB) for 4 weeks and they are fractioned using ethyl acetate and butanol. Ethyl acetate and butanol extracts were analyzed for antibacterial activity. The fungi strains which showed the maximum activity were identified by macroscopic and microscopic examination. Twelve (50%) extracts of endophyte fungi strains were able to inhibit the growth of pathogenic bacteria such as, Staphylococcus aureus and Escherichia coli. Endophytic fungi strains that have higher antibacterial activity derived from the root than from leave and bark Sonneratia griffithii Kurz. This work concluded that endophytic fungi strains of Sonneratia griffithii Kurz can be developed as a new source of antibiotic compounds.
Keywords: Endophytic fungi, mangrove, Sonneratia griffithii Kurz, antibacterial activity.